Current state of practice regarding digital radiography exposure indicators and deviation indices: Report of AAPM Imaging Physics Committee Task Group 232. Issue 11 (17th October 2018) - Dave, Jaydev K.; Jones, A. Kyle; Fisher, Ryan; Hulme, Katie; Rill, Lynn; Zamora, David; Woodward, Andrew; Brady, Samuel; MacDougall, Robert D.; Goldman, Lee; Lang, Susan; Peck, Donald; et al.
Abstract : Beginning with the advent of digital radiography systems in 1981, manufacturers of these systems provided indicators of detector exposure. These indicators were manufacturer‐specific, and users in facilities with equipment from multiple manufacturers found it a challenge to monitor and manage variations in indicated exposure in routine clinical use. In 2008, a common definition of exposure index (EI) was realized in International Electrotechnical Commission (IEC) International Standard 62494‐1 Ed. 1, which also introduced and defined the deviation index (DI), a number quantifying the difference between the detector EI for a given radiograph and the target exposure index (EIT ). An exposure index that differed by a constant from that established by the IEC and the concept of the deviation index also appear in American Association of Physicists in Medicine (AAPM) Report No. 116 published in 2009. The AAPM Report No. 116 went beyond the IEC standard in supplying a table (Table II in the report of TG‐116) titled "Exposure Indicator DI Control Limits for Clinical Images, " which listed suggested DI ranges and actions to be considered for each range. As the IEC EI was implemented and clinical DI data were gathered, concerns were voiced that the DI control limits published in the report of TG‐116 were too strict and did not accurately reflect clinical practice. The charge of task group 232 (TG‐232) and the objective of this final report was to investigate the current state of the practice for CR/DR Exposure and Deviation Indices based on AAPM TG 116 and IEC‐62494, for the purpose of establishing achievable goals (reference levels) and action levels in digital radiography. Data corresponding to EI and DI were collected from a range of practice settings for a number of body parts and views (adults and pediatric radiographs) and analyzed in aggregate and separately. A subset of radiographs was also evaluated by radiologists based on criteria adapted from the European Guidelines on Quality Criteria for Diagnostic Radiographic Images from the European Commission. Analysis revealed that typical DI distribution was characterized by a standard deviation (SD) of 1.3–3.6 with mean DI values substantially different from 0.0, and less than 50% of DI values fell within the significant action limits proposed by AAPM TG‐116 (−1.0 ≤ DI ≤ 1.0). Recommendations stemming from this analysis include targeting a mean DI value of 0.0 and action limits at ±1 and ±2 SD of the DI based on actual DI data of an individual site. EIT values, DI values, and associated action limits should be reviewed on an ongoing basis and optimization of DI values should be a process of continuous quality improvement with a goal of reducing practice variation.